Peran Guru dalam Mewujudkan Pembelajaran yang Berpusat pada Peserta Didik melalui Kurikulum Merdeka - Devy Maria Sari; Cantika Humaira; Elvita Ayu Simanjuntak; Putri Rahmadhani Oktapianti; Soviyola Soviyola; Nevrita Yudi Pratama (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
Education in Indonesia continues to face significant challenges in transforming its curriculum to meet 21st-century competency demands, especially with the implementation of the Merdeka Curriculum, which emphasizes flexibility, contextual learning, and a student-centered approach. This study aims to analyze teachers’ roles in implementing student-centered learning, identify the challenges they encounter, and examine strategies used to address these obstacles. Using a qualitative library research method, the study reviews primary and secondary literature related to student-centered learning theory, learning experiences, authentic assessment, and the implementation of the Merdeka Curriculum. Findings show that teachers serve as the central factor in ensuring the success of active and student-centered learning. Those who are adaptive and innovative are able to design meaningful learning experiences even when confronted with limited facilities, diverse student needs, and classroom management constraints. Nevertheless, many teachers still struggle with differentiated instruction, authentic assessment, and the flexible learning management required by the Merdeka Curriculum. This study underscores the need to improve teachers’ pedagogical competence, provide sufficient learning resources, and develop responsive educational policies to strengthen the overall implementation of the Merdeka Curriculum in schools.